The Using of English Animation Movie to Improve Students’ Listening Achievement in the New Normal Era - May Saroh Jati Rahayu; Endang Mastuti Rahayu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2023)
This study aimed at proving whether or not English animation movies could improve students’ listening achievement in SMA Negeri 1 Driyorejo. According to the findings of the pra-cycle of observations, Bahasa students of SMA Negeri 1 Driyorejo had problems assimilating the lesson materials. It was caused by the students' lack of vocabulary and they did not understand what native speakers said. In obtaining the data, there were 35 students contained 9 males and 26 females in Bahasa Class at SMA Negeri 1 Driyorejo. This study used classroom action research. The data in this study were observation, test, and questionnaire. The data analysis techniques used were descriptive qualitative. There were three steps such as pra-cycle, cycle I, and cycle II for collecting the data. The result showed the use of animated movies as media had greatly improved students' listening skills. It was found by comparing the result of pre-test, post-test I, and post-test II. Based on the data obtained, the researcher concluded that students’ listening achievement improved after using English animation movie. Students who reached the minimum score criteria were 3% for pre-test, 46% for post-test I, and 77% for post-test II.